PERSAINGAN, GESEKAN, DAN PERTUMBUHAN PARIWISATA: STUDI KASUS KINAHREJO - Tanaamah, Andeka Rocky; Prabawa, Titi Susilowati; Rupidara, Neil Semuel (KRITIS, 2017)
Tourism is a potential economic sector that contributes to more sustainable economic growth. Not only focusing on economic growth, tourism has also been proven in improving livelihoods as well as increasing benefits for local communities. Tourism can however be a field of rivalry or tension in the society. This article aims to analyse rivalry and clash happen among tourism actors and other elements of the society in Kinahrejo, also with government, which is caused by the growth of tourism in Kinahrejo. Emerging dark tourism in Kinahrejo has stimulated the growth of relevant businesses. However,the growth of tourism has also led to competition and friction in the management of local resources. This study looks at three forms of friction that occur in the management of Kinahrejo tourism assets. First, friction between the tourism actors in Kinahrejo caused by the desire to control the tourism resources. Second, friction between tourism business and stone sand mining business, caused by the lucrative offer of income. Third, friction with the government related to the relocation policy of the people of kinahrejo to a safer place and avoid the eruption of Mount Merapi. Completion of friction is done by optimizing the role of the community association in facilitating relationships between the various groups involved in tensions.